Structural characterization of novel cassava starches with low and high-amylose contents in comparison with other commercial sources - Rolland Sabaté, Agnès; Sánchez, Teresa; Buleon, A; Colonna, PC; Jaillais, B; Ceballos, H.; Dufour, D.L. (Elsevier, 2011)
Two new mutant cassava starches with extreme amylose contents (0 and 30 31%) have been recently reported. These mutants are drastically different from normal cassava starch whose amylose content typically ranges between 15 and 25%. The new mutants were compared with five normal cassava starches (ranging from 16.8 to 21.5% amylose) and commercial versions of amylose-free or normal potato and maize starch. Macromolecular features, crystallinity, granule sizes, and thermal properties of these starches were compared. The structure of cassava amylopectin was not modified by the waxy mutation and waxy cassava starch exhibited properties similar to the ones of waxy maize starch. Waxy cassava and maize show similar View the MathML source and View the MathML source of amylopectin (between 408 × 106 g mol?1 and 520 × 106 g mol?1; 277 285 nm, respectively), whereas waxy potato amylopectin has lower View the MathML source and View the MathML source. On the contrary, the higher-amylose mutations induced by gamma rays radiation in cassava, modified deeply the branching pattern of amylopectin as well as the starch characteristics and properties: View the MathML source and View the MathML source decreased, while branching degree increased. These modifications resulted in changes in starch granule ultrastructure (e.g. decreased starch crystallinity), a weak organized structure, and increased susceptibility to mild acid hydrolysis. The distinctive properties of the new cassava starches demonstrated in this article suggest new opportunities and commercial applications for tropical sources of starch.